Aspirin Desensitization in Patients With Coronary Artery Disease: Results of the Multicenter ADAPTED Registry (Aspirin Desensitization in Patients With Coronary Artery Disease). (February 2017) - Rossini, Roberta; Iorio, Annamaria; Pozzi, Roberto; Bianco, Matteo; Musumeci, Giuseppe; Leonardi, Sergio; Lettieri, Corrado; Bossi, Irene; Colombo, Paola; Rigattieri, Stefano; Dossena, Cinzia; Anzuini, Angelo; et al.
Abstract : Background—: There are limited data on aspirin (ASA) desensitization for patients with coronary artery disease. The aim of the present study was to assess the safety and efficacy of a standard rapid desensitization protocol in patients with ASA sensitivity undergoing coronary angiography. Methods and Results—: This is a prospective, multicenter, observational study including 7 Italian centers including patients with a history of ASA sensitivity undergoing coronary angiography with intent to undergo percutaneous coronary intervention. A total of 330 patients with history of ASA sensitivity with known/suspected stable coronary artery disease or presenting with an acute coronary syndrome, including ST-segment–elevation myocardial infarction were enrolled. Adverse effects to aspirin included urticaria (n=177, 53.6%), angioedema (n=69, 20.9%), asthma (n=65, 19.7%), and anaphylactic reaction (n=19, 5.8%). Among patients with urticaria/angioedema, 13 patients (3.9%) had a history of idiopathic chronic urticaria. All patients underwent a rapid ASA (5.5 hours) desensitization procedure. The desensitization procedure was performed before cardiac catheterization in all patients, except for those (n=78, 23.6%) presenting with ST-segment–elevation myocardial infarction who underwent the desensitization after primary percutaneous coronary intervention. Percutaneous coronary intervention was performed in 235 patients (71%) of the overall study population. The desensitization procedure was successful in 315 patients (95.4%) and in all patients with a history of anaphylactic reaction. Among the 15 patients (4.6%) who did not successfully respond to the desensitization protocol, adverse reactions were minor and responded to treatment with corticosteroids and antihistamines. Among patients with successful in-hospital ASA desensitization, 253 patients (80.3%) continued ASA for at least 12 months. Discontinuation of ASA in the 62 patients (19.7%) who had responded to the desensitization protocol was because of medical decision and not because of hypersensitivity reactions. Conclusions—: A standard rapid desensitization protocol is safe and effective across a broad spectrum of patients, irrespective of the type of aspirin sensitivity manifestation, with indications to undergo coronary angiography with intent to perform percutaneous coronary intervention. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02848339.